The deadly shallows - Pettrey, Dani (Pettrey, Dani. Coastal guardians, 2022)
"Coast Guard Flight Medic Brooke Kesler was caught in a mass shooting at a Coast Guard graduation-and little does she know that she overheard something that could expose the mastermind's identity. With targets on their backs, Brooke and her boyfriend CGIS Agent Noah Rowley must race to find the killer before he strikes again"--